El grado de orientación pro-pobre de las políticas económicas peruanas: una revisión bibliográfica - Francke, Pedro (2005)
This paper is a balance of the Peruvian economic policies, taken by government inthe last decade. We focus on determining, based on the available literature, whetheror not these polices have improved the economic well-being of poor people. Furthermore, this balance allow us to give the agenda for future research on these areas, aswell as to shed some light about the pro-poor necessary policies. There are several policies that have been taken into account in this balance. Macroeconomicpolicies; trade and investment policies; specific sector promotion policies(agriculture, industry and mining sector); labor (both formal and informal), capitaland land markets; regulation of goods and services markets (telecommunications andelectricity); taxation policies; public expenditure; security and risk management mechanismsand, finally, regional policies.